Waste paper to bioethanol: Current and future prospective. (15th March 2019) - Al‐Azkawi, Ahlam; Elliston, Adam; Al‐Bahry, Saif; Sivakumar, Nallusamy
Abstract: Bioethanol is considered to be a possible substitute for non‐renewable fossil fuels. Biofuels, including bioethanol, are gradually replacing coal and oil for energy production. It is expected that, by 2040, fossil fuels' contribution to the world's energy demands will only be 25% with the remaining contribution made up by biofuels. One of the major factors affecting ethanol production is the cost of raw materials, which can be substantially reduced by utilizing industrial or agricultural lignocellulosic wastes. Using waste paper as a feedstock for bioethanol production would reduce the production cost and may eliminate problems in managing this waste material in the environment. The cellulose, hemicellulose, and lignin in waste paper are less complicated and so only mild pretreatment is needed before enzymatic hydrolysis and fermentation. This review covers topics such as bioethanol as a promising alternative to petroleum fuels, feedstocks for bioethanol production, lignocellulosic technology and challenges for ethanol production, advantages and disadvantages of pretreatments methods, waste paper as feedstock for ethanol production, processing of waste paper to ethanol, and the different integration methods of hydrolysis and fermentation. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.